Pengembangan Handout Logan Avenue Problem Solving (LAPS-Heuristik) Bermuatan Multi Representasi untuk Meningkatkan Kemampuan Bahasa Simbolik Peserta Didik Kelas XI - Siti Rokhimah; Siska Desy Fatmaryanti; Nurhidayati Nurhidayati (Radiasi : Jurnal Berkala Pendidikan Fisika, 2018)
Research and development (R&D) have been conducted to determine the feasibility of the handout, to learn about the improvement of students 'symbolic language skills after using the handout, and to know the students' responses to the handout. The subjects of this study were students of class XI IPA 1 of SMA Negeri 1 Binangun, with data collection techniques using observation, interviews, questionnaires, tests, and documentation. The data obtained in the form of qualitative and quantitative data, while the data analysis with percent values, Percentage Agreement, and normalized gain. Based on the results of the study obtained a mean score of validation results by three validators of 3.53 with good criteria so that the LAPS-Heuristic handout with multi representation is feasible to be used in physics learning with a little revision. The average implementation of learning by using data analysis techniques Percentage Agreement of two observers by 97% with very good criteria. The test results of students' responses to the use of the multi-representation LAPS-Heuristic handout states that the handout is included in either criterion with a score of 3.42 or expressed as a percentage of 85%. The use of the multi-representation LAPS-Heuristic handout can improve the students' symbolic language abilities by obtaining a normalized gain value of 0.73 which is included in the high criteria. Thus, Logan Avenue Problem Solving (LAPS-Heuristics) Handout Loaded Multi Representations to Improve Symbolic Language Ability of Class XI Students can be categorized well and fit for use as alternative teaching material in high school physics learning that is able to improve the symbolic language skills of students.